2018
DOI: 10.1002/mbo3.590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydraulic retention time on microbial community structure in wastewater treatment electro‐bioreactors

Abstract: The impact of hydraulic retention time (HRT) on the performance and microbial community structure of control and electro‐bioreactors was investigated. Control bioreactors and electro‐bioreactors were operated at HRT ranging between 6 and 75 hr. The total bacterial counts in addition to the removal efficiency of NH 4 +–N, sCOD, and PO 4 3−–P was assessed in all the reactors tested. In addition, Illumina sequencing was performed to determine the microbial communities that developed in these reactors under each H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Proteobacteria (19%-52%) was the most abundant species. This result could be linked to a previous study [54,55] that, confirmed that Betaproteobacteria could be classified as the one dominant group in the ecosystem of streams during May, August, and October. Our investigation showed that Bacteroidetes did not appear in May (abundance >1%), suggesting that Bacteroidetes was present in low numbers, was missed in those selected points, or did not perfectly amplify with the PCR primers.…”
Section: Discussionsupporting
confidence: 84%
“…Proteobacteria (19%-52%) was the most abundant species. This result could be linked to a previous study [54,55] that, confirmed that Betaproteobacteria could be classified as the one dominant group in the ecosystem of streams during May, August, and October. Our investigation showed that Bacteroidetes did not appear in May (abundance >1%), suggesting that Bacteroidetes was present in low numbers, was missed in those selected points, or did not perfectly amplify with the PCR primers.…”
Section: Discussionsupporting
confidence: 84%
“…Subsequently, the removal efficiency was increased (Singh & Srivastava, 2011). HRT, an important operator, affects the performance and microbial community in biological systems (ElNaker et al, 2018). Moreover, the removal yields of BOD 5 , PO 4 ‐P, N‐NH 3 , and color were obtained 94.72%, 97.39%, 57.14%, and 25.93%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The TBC was performed in duplicate and an average value was reported. The detailed procedure of this experiment has been described previously . The difference between the TBC concentration in the feed ( C f ) and the permeate ( C p ) represents the TBC removal percentage as shown in Eqn (4): TBC0.25emremoval0.25em()%=CfCpCf0.25em×100 …”
Section: Methodsmentioning
confidence: 99%
“…The detailed procedure of this experiment has been described previously. 30 The difference between the TBC concentration in the feed (C f ) and the permeate (C p ) represents the TBC removal percentage as shown in Eqn (4):…”
Section: Seawater Quality Analysis and Membrane Performance Testsmentioning
confidence: 99%